Strengthening Digital-Based Community Political Literacy in the Prevention of Money Politics in South Bangka Regency - Annisa Nur Syafitri; Astika Ummy Athahirah; Herlina (Jurnal Multidisiplin Madani, 2024)
The high number of money politics in 2019 in South Bangka Regency affects the increasing vulnerability of money politics during the 2024 election period. The General Election Supervisory Agency (Bawaslu) in the 2019 general election stated that South Bangka Regency is ranked in the top 20 areas prone to money politics and ranks 18th in Indonesia in the 2024 general election and the second highest money politics in the Bangka Belitung Islands Province. This study aims to determine the urgency of political literacy in preventing money politics in the South Bangka Regency and to obtain an overview of efforts to strengthen people's political literacy in preventing money politics. This study used Quasi-Qualitative Design (QQD). Data were obtained through observation, interviews, and documentation. The data was processed using triangulation of data collection techniques. The study shows that the political literacy of the community in the prevention of money politics in South Bangka Regency is still very worrying because the lack of public knowledge related to the government structure, low interest in news and political issues, and low public understanding of money politics and its implications for democracy. Therefore, we suggest cooperation between stakeholders, especially in this digital era, is essential in increasing political literacy and preventing money politics